Penerapan Konseling Kelompok Teknik Self Control Dalam Mengatasi Perilaku Prokrastinasi Menghafal Al-Qur’an Pada Santriwati - Syahrani Ayu Alia Firdaus; Abdur Razzaq; Hartika Utami Fitri (ScidacPlus, 2023)
Memorization lessons are not extracurricular lessons like those in public schools, but are one of the main lessons in Islamic boarding schools. The Qur'an is the book and the main reference for Muslims and Muslims are obliged to believe in it as one of the pillars of faith. One way to believe in the books of Allah SWT, namely the Al-Qur'an is to read and understand its contents as a guide for Muslims in order to achieve safety and happiness in this world and the hereafter. Al-Furqon Modern Islamic Boarding School where memorizing the Qur'an is a form of class promotion and graduation requirement. Memorizing the Qur'an the students are also still required to attend formal school, organizational activities, and activities held by the boarding school. Santri who study in pesantren are on average in the adolescent age range with various characteristics. Like teenagers in general, santri also have common problems that are often faced, one of which is learning problems. Learning is a task that must be done by every individual, but not all individuals have good or effective learning management, especially in the problem of time management, this is also often experienced by many students. Self Control is the ability of individuals to read the situation of themselves and their environment. It is also the ability to control and manage behavioral factors in accordance with the situation and conditions in order to be able to display a good personality with positive behavior in memorizing the Qur'an. Self Control can also help individuals to control emotions or regulate behavior in order to adapt to the environment in a positive direction in overcoming these problems. One of them occurs frustration when procrastinating in memorizing the Qur'an. Therefore, through this research the author will examine how to apply group counseling Self Control Techniques in Overcoming Procrastination Behavior in Memorizing Al-Qur'an in Santriwati at Al-Furqon Islamic Boarding School with a qualitative research method as a research procedure that produces descriptive data in the form of written and spoken words from people or observable behavior and circumstances that are happening.